When to look at maps in navigation: metacognitive control in environment learning. - Dai, Ruizhi.; Thomas, Ayana K.; Taylor, Holly A. (Tufts Archival Research Center, 2018)
A qualifying paper submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Education. Abstract: People learn environments through direct experience with the environment and/or through map study. Further, the different perspectives taken while learning an environment influence the knowledge acquired. After all, different information about an environment is readily available through route (e.g. by navigation) and survey (e.g. with maps) perspectives. Having a choice between direct experience and map use, or between different perspectives, suggests a role of metacognitive control in environment learning. That is, when in a new environment, learners may exercise metacognitive control by selectively choosing and implementing specific learning strategies, such as switching between perspectives. Strategy choice may depend on specific constraints, such as perspective, range of view, or amount of time to learn (to name a few). For example, people may check a map (e.g. on smartphones or GPS devices) to complement developing route knowledge. The present review discusses the role of metacognition in environment learning and outlines new directions for research to bridge these fields by examining how strategic metacognitive control over perspective switching affects environment learning. Such explorations can inform real-world environment learning and navigational aids design.